2020
DOI: 10.1002/slct.202001268
|View full text |Cite
|
Sign up to set email alerts
|

Green EmittingCe3+/ Tb3+‐Doped BaF2 Nanocrystals and Their Impact on Skeletal Muscle of Developing Zebrafish Larvae

Abstract: An ionic liquid (IL)-based solvothermal method is employed to prepare single-phase, luminescent, cubic rare-earth doped and silica-coated BaF 2 nanomaterials. High energy transfer efficiency (∼ 60%) from Ce 3 + to Tb 3 + for BaF 2 :Ce 3 + /Tb 3 + nanoparticles dispersed in DMSO solution is observed. Furthermore, for the first time to the best of our knowledge, as-prepared RE ion/s doped and silica-coated BaF 2 nanoparticles are used for the toxicological assessment on live zebrafish larvae. Interestingly, stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Crystallite sizes are measured using the Debye–Scherer equation, and it is observed that the concentrations of dopant ions have a significant effect on crystallite size (Table S1). In addition, the lattice strain of as-synthesized rare-earth ion-doped nanophosphors is also calculated using the Williamson–Hall equation. Tensile strain is obtained in all cases for the as-prepared undoped and (Er 3+ /Yb 3+ )-doped BaGdF 5 nanophosphors (Figures S1 and S2 and Table S1).…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Crystallite sizes are measured using the Debye–Scherer equation, and it is observed that the concentrations of dopant ions have a significant effect on crystallite size (Table S1). In addition, the lattice strain of as-synthesized rare-earth ion-doped nanophosphors is also calculated using the Williamson–Hall equation. Tensile strain is obtained in all cases for the as-prepared undoped and (Er 3+ /Yb 3+ )-doped BaGdF 5 nanophosphors (Figures S1 and S2 and Table S1).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Ionic liquid, which is considered as a “green and designer” solvent, can play a major role in nanomaterial synthesis due to its negligible vapor pressure, high viscosity, non-flammability, large electrochemical window, catalytic nature, etc. In this article, we report the synthesis of upconverted rare-earth ion(s)-doped (i.e., RE 3+ = Yb 3+ /Er 3+ ) BaGdF 5 nanocrystals via the ionic liquid-assisted hydrothermal method where IL [C 4 mim]­BF 4 can be used as a solvent, reaction partner (fluorinating agent), and templating agent/capping agent, i.e., “all three in one” (Figure ) and details are given in the Supporting Information. Analysis reveals that upconversion intensity is influenced by dopant concentrations, and finally, upconverted nanophosphors are used in device application for the DSSC.…”
Section: Introductionmentioning
confidence: 99%
“…Several past studies have shown that the craniofacial development in zebrafish embryo is sensitive towards the presence of estrogen hormone, [75] endocrine disrupting compounds like Atrazine herbicide, [76] polycyclic aromatic hydrocarbons, [77] teratogens [78] and even various types of nanoparticles like lanthanide doped BaF 2 nanophosphors, Silica or Nickel based nanoparticles. [54,57,[79][80][81][82][83] Therefore, in this study, we have also employed craniofacial development as a sensitive biomarker to screen the synergistic behavior of nanocomponents (GO or BG3) and their nanocomposites (BG4 or BG5) at 50 and 150 mg/L. The cartilage consists solely of chondrocyte cells; Ant and Ven indicates the Anterior and Ventral direction in the images of zebrafish larvae.…”
Section: Nanoparticles' Effect On the Craniofacial Cartilage Developm...mentioning
confidence: 99%